Study from home and stress level among school-age children - Astutik, Endang Fidya; Mareta, Reni; Handayani, Estrin (Universitas Muhammadiyah Magelang, 2024)
The COVID-19 pandemic necessitated a shift to online learning or study from home (SFH), which introduced a range of psychological stressors and associated challenges. This study investigated the correlation between stress levels and SFH among students. Utilizing an observational study design, the research included 241 respondents. Various validated instruments were employed to measure the scores of each variable and ethical clearance was secured before the study commenced. Spearman rank testing was conducted to assess the correlation between stress and SFH. The results demonstrated a significant correlation, indicating that studying from home contributes to heightened stress levels among students. Based on these findings, it is recommended that community healthcare professionals develop and implement interventions that specifically address the psychological well-being of students engaged in home-based learning. Keywords: Nursing care; community care; innovation care; learning method; study from home